Determinação de compostos bioativos em amostras comerciais de café torrado Determination of bioactive compounds in Brazilian roasted coffees - Mariana Costa Monteiro (Química Nova, 2005)
Coffee is a product consumed all around the world, Brazil being the biggest exporter. However, little is known about the difference in composition of the different brands in terms of bioactive substances. In the present study, ten of the most consumed brands of coffee in Rio de Janeiro were analyzed. Caffeine contents, trigonelline and total chlorogenic acid varied from 0.8 g/100g to 1.4 g/100g; 0.2 g/100g to 0.5 g/100g and from 3.5 g kg-1 to 15.9 g kg-1, respectively. The large heterogeneity observed in the amounts of the bioactive compounds can be attributed to different formulations of the various brands, as well as to different roasting conditions.